Identifikasi Bahaya Perencanaan Proyek Renovasi Gedung Hotel Horison Express Fatmawati Jakarta - Dhika Febrizal; Nia Kartika (Jurnal Talenta Sipil, 2023)
The implementation of construction development is an activity that causes many elements of danger, so it has a risk of work accidents. Factors that cause work accidents, ranging from a lack of employee discipline in maintaining occupational health and safety. This identification aims to assess the risks in the Planning of the Horison Express Hotel Building Renovation Fatmawati Jakarta, using a questionnaire with a frequency value (F) and a severity value (A), the results of the identification of the IBPRP method there are work items with a moderate level of risk in the Lt. 1-4 the relative risk value is obtained with a value of 9 (medium), and the work with a high level of risk is in the Lt. Structural Work. 5-6 relative risk values obtained Value of 20 (High), the results of the identification there are 58 basic events that cause the basic risk of 26 items of work, obtained a presentation of the value of low risk level of: 50%, moderate risk level of: 46.5%, and high risk level of: 3.5%. For hazard identification methods other than using the IBPRP method, can use other hazard identification methods for research on the same theme.